2009
DOI: 10.1111/j.1083-6101.2009.01494.x
|View full text |Cite
|
Sign up to set email alerts
|

Facebook and Online Privacy: Attitudes, Behaviors, and Unintended Consequences

Abstract: This article investigates Facebook users' awareness of privacy issues and perceived benefits and risks of utilizing Facebook. Research found that Facebook is deeply integrated in users' daily lives through specific routines and rituals. Users claimed to understand privacy issues, yet reported uploading large amounts of personal information. Risks to privacy invasion

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

27
596
3
22

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 945 publications
(694 citation statements)
references
References 24 publications
27
596
3
22
Order By: Relevance
“…Budući da su novi mediji višestruko povećali količinu robe na tržištu privatnosti, njena cijena je počela padati. Obični ljudi počinju da žive javne živote u kući "velikog brata", kao i u brojnim drugim emisijama u kojima iznose detalje o svojim privatnim životima, nude svoju privatnost na kamerama na internetu i, sve češće, objavljuju svoje privatne živote na jutjubu i u širokim krugovima svojih prijatelja na fejsbuku i drugim društvenim mrežama (Debatin, Lovejoy, Horn, i Hughes, 2009). Posebno je, svakako, zanimljivo sužavanje privatnosti na društvenim mrežama koje zagovaraju digitalna okruženja za vođenje privatnih života, a koja su praktično dostupna svakom.…”
Section: Osobine Kulture Novog Posredništvaunclassified
“…Budući da su novi mediji višestruko povećali količinu robe na tržištu privatnosti, njena cijena je počela padati. Obični ljudi počinju da žive javne živote u kući "velikog brata", kao i u brojnim drugim emisijama u kojima iznose detalje o svojim privatnim životima, nude svoju privatnost na kamerama na internetu i, sve češće, objavljuju svoje privatne živote na jutjubu i u širokim krugovima svojih prijatelja na fejsbuku i drugim društvenim mrežama (Debatin, Lovejoy, Horn, i Hughes, 2009). Posebno je, svakako, zanimljivo sužavanje privatnosti na društvenim mrežama koje zagovaraju digitalna okruženja za vođenje privatnih života, a koja su praktično dostupna svakom.…”
Section: Osobine Kulture Novog Posredništvaunclassified
“…Fakat literatüre bakıldığında sürekli değişen rakamlar, ölçüm yöntemlerinin sınırlılığı ve üretilmiş ampirik teorilerin yetersizliği nedeniyle özellikle gelişmekte olan ülkeler için yeni sosyal medya çalışmalara ihtiyaç olduğu gözlemlenmektedir. Literatürdeki kimi çalışmalar Facebook'un kullanıcılarının davranışları üzerine etkisi üzerineyken (Ryan, Xenos, 2011& Ellison, Steinfield, Lampe, 2007& Orr, Sisic, Ross, Simmering, Arseneault, Orr, 2009& Wyche, Schoenebeck, Forte, 2013& Hughes, Rowe, Batey, Lee, 2012, kimi çalışmalar da Facebook ve mahremiyet kavramları üzerinedir (Dwyer, Hiltz, Passerini, 2007& Debatin, Lovejoy, Horn, Hughes, 2009. Günümüzde ise Facebook'u tüketici odaklı ve interaktif iletişim kanalı kullanan şirketler de tüketicilerinin şirketin profil sayfası, güncellemeleri, diğer tüketicilerin yorumları, ürün bilgileri hakkında ne düşündüğü ve kaç müşterinin sayfayı beğendiği (like) gibi konular hakkında bilgi sahibi olmak istediği görülmektedir (Hansson, Wrangmo, Soilen, 2013:120-121).…”
Section: Facebookunclassified
“…Although studies have demonstrated that the public nature of SNS remains unclear to many users (Stutzman, 2006) and that there is a fundamental discrepancy between users' desire for privacy protection and their actual behaviour (Acquisti & Gross, 2006), questions of privacy and integrity are most often discussed without taking back-end processes of monitoring into account (Andrejevic, 2011). Rather, these matters have been treated by paying attention to complicated privacy settings and the difficulties associated with upholding personal integrity online (see also Dwyer et al, 2007;Debatin et al, 2009). …”
Section: Egocentric Network and Individual-oriented Agencymentioning
confidence: 99%